Representation of transmission lines in modal domain using analytical transformation matrices - Carvalho, C. G. [UNESP]; Souza, N. V. [UNESP]; Kurokawa, S. [UNESP]; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
The phases of a transmission line are tightly coupled due to mutual impedances and admittances of the line. One way to accomplish the calculations of currents and voltages in multi-phase lines consists in representing them in modal domain, where its n coupled phases are represented by their n propagation modes. The separation line in their modes of propagation is through the use of a modal transformation matrix whose columns are eigenvectors associated with the parameters of the line. Usually, this matrix is achieved through numerical methods which does not allow the achievement of an analytical model for line developed directly in the phases domain. This work will show the modal transformation matrix of a hypothetical two-phase obtained with numerical and analytical procedures. It will be shown currents and voltage s at terminals of the line taking into account the use of modal transformation matrices obtained by using numerical and analytical procedures. © 2011 IEEE.
Keywords: Modal domain; Newton-Raphson; transformation matrix; transmission line; two-phase line; Transformation matrices; Bandpass filters; Electric lines; Mathematical models; Numerical methods; Transmission line theory; Linear transformations